Diagnostic accuracy of capnography during high‐frequency ventilation in neonatal intensive care units. Issue 5 (30th September 2015) - Kugelman, Amir; Bromiker, Ruben; Riskin, Arieh; Shoris, Irit; Ronen, Michal; Qumqam, Nelly; Bader, David; Golan, Agenta
Summary: Background and Objective: High‐frequency ventilation (HFV) is a powerful tool for CO2 elimination, and thus requires careful monitoring of CO2 . Our aim was to assess the diagnostic accuracy (correlation, agreement, and trending) of continuous distal capnography (dCap) with PaCO2 in infants ventilated with HFV. Design: This was a prospective, observational, multicenter study. dCap was compared with simultaneous PaCO2 ("gold standard") drawn from indwelling arterial line for patient care in term and preterm infants ventilated with HFV. dCap was obtained via the side‐port of a double‐lumen endotracheal‐tube by a Microstream capnograph with specially designed software for HFV. Results: Twenty‐four infants participated in the study (median [range] gestational age [GA]: 26.8 [23.6–38.6] weeks). Analysis included 332 measurements. dCap was in correlation (r = 0.70, P  < 0.001) but with less than adequate agreement (mean difference ± SD of the differences: −11.7 ± 10.3 mmHg) with PaCO2 . Comparable findings were found in the subgroup of infants <1, 000 g (n = 240 measurements). Correlations were maintained in severe lung disease. Changes in dCap and in PaCO2 for consecutive measurements within each patient were correlated (r = 0.63, P  < 0.001). Area under the receiver operating curves (ROC) for dCap to detect high (>60 mmHg) or low (<30 mmHg) PaCO2 was 0.83 (CI: 0.76–0.90) and 0.88 (CI: 0.79–0.97), respectively; P  < 0.001. Conclusions: Our prospective study suggests that continuous dCap in infants ventilated with HFV may be helpful for trends and alarm for unsafe levels of PaCO2 . dCap is only a complimentary tool and cannot replace PaCO2 sampling because the agreement between these measurements was less than adequate.Pediatr Pulmonol. 2016;51:510–516 . © 2015 Wiley Periodicals, Inc.